[18F]-fluorodeoxyglucose positron emission tomography of the cat brain: A feasibility study to investigate osteoarthritis-associated pain. Issue 3 (June 2015) - Guillot, Martin; Chartrand, Gabriel; Chav, Ramnada; Rousseau, Jacques; Beaudoin, Jean-François; Martel-Pelletier, Johanne; Pelletier, Jean-Pierre; Lecomte, Roger; de Guise, Jacques A.; Troncy, Eric
Highlights [18F]-fluorodeoxyglucose positron emission tomography of the cat brain. Brain metabolism of osteoarthritic cats is increased in pain key regions. Brain plasticity occurred in natural OA-associated pain in cats. Sustained nociceptive inputs are present in feline OA-associated pain. Increased activity of the descending pathways is present in feline OA-associated pain.